Energetic efficiency programs and power quality - De Oliveira, L C O; De Melo, G. A.; Rossi, J. C.; Scicuglia, J. W.; Dantas, J. D.; Penna, C.; Ajeje, P. C. (IEEE, 2002)
This paper presents the results of the investigations that were done to identify and to quantify the power quality problems resultant from the actions done to improve the efficiency on electric energy consumption. The efficiencies of several electric devices were evaluated, among them: fluorescent bulb, electronic ballast, soft-starter, temperature controller for showers, dimmer and others. This evaluation allowed to establish a cause/effect analysis of the power quality.
Keywords: efficiency; power quality; harmonics